Diagnosis of epidermoid carcinoma of the tongue after treatment of epidermoid carcinoma of the esophagus - Marília Ferreira Andrade; Luiz Carlos Takita; Pâmela Ferreira De Sá Queiroz; Regina Maria Raffaele; Mario Eduardo Baldo; Rondon Tosta Ramalho (Wolters Kluwer Medknow Publications, 2023)
In the present case report, a patient with esophageal squamous cell carcinoma (SCC) developed a second primary tumor in the tongue at the same time. Stage III middle esophageal SCC was discovered in a 60-year-old Caucasian male patient who was institutionalized, a smoker, and had previously struggled with alcoholism. Following treatment, the patient was admitted to the hospital for 15 days due to dysphagia and malnutrition. According to him, he had mouth pain while in the hospital. An intraoral examination revealed tooth mobility, bacterial plaque, dental calculus, and a 1.3-cm ulcerated lesion on the right lateral edge of the tongue. During the extraoral examination, no palpable lymph nodes were found in the submandibular or cervical regions. The tongue lesion was excisionally biopsied, and the histological evaluation agreed. The patient was advised to seek treatment for tongue SCC. Given that patients with esophageal SCC have a 9.3%-11.4% risk of developing head-and-neck SCC, multiprofessional follow-up of patients with esophageal SCC is critical for early detection of this cancer.